2020
DOI: 10.1038/s41598-020-62579-7
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin affects IRS1/Akt signaling and prevents high glucose-induced apoptosis in podocytes

Abstract: Diabetes-induced podocyte apoptosis is considered to play a critical role in the pathogenesis of diabetic kidney disease (DKD). We proposed that hyperglycaemia can induce podocyte apoptosis by inhibiting the action of podocyte survival factors, thus inactivating the cellular effects of insulin signalling. In this study, we aimed to determine the effects of linagliptin on high glucose-induced podocyte apoptosis. Linagliptin reduced the increase in DNA fragmentation as well as the increase in TUNEL-positive cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…One limitation of our study is that we did not establish a model of sepsis induced by real pathogens, which limits the application of our findings to patients in the clinical context. Another limitation is that we did not test linagliptin at a lower concentration; as low as 50 nM has shown protective effects in vitro [ 32 , 33 ]. Additional work is needed to investigate the potential toxicity or benefits of different linagliptin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is that we did not establish a model of sepsis induced by real pathogens, which limits the application of our findings to patients in the clinical context. Another limitation is that we did not test linagliptin at a lower concentration; as low as 50 nM has shown protective effects in vitro [ 32 , 33 ]. Additional work is needed to investigate the potential toxicity or benefits of different linagliptin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-4 inhibitors can reduce inflammation and decrease MCP-1 levels ( Hung et al., 2020 ). Both DPP-4 and GLP-1 elicit vasotropic effects and decrease diabetes-induced oxidative stress in the glomerulus, ameliorating DKD ( Mima et al., 2020 ) ( Mima et al., 2012a ). Recent studies have shown that sitagliptin treatment activates the transcription factor cAMP response element-binding protein (CREB), which increases β cell mass or islet angiogenesis ( Samikannu et al., 2013 ).…”
Section: Dkd Therapy Targeting Oxidative Stress and Mitochondrial Fun...mentioning
confidence: 99%
“…We have reported that GLP-1 increased by DPP-4 inhibitors can activate adenylyl cyclase, promote cAMP production, and foster PKA activation, which subsequently induces serine phosphorylation of CREB ( Mima et al., 2012a ). Interestingly, linagliptin was shown to increase anti-oxidative stress effects in podocytes by increasing Nrf2 ( Mima et al., 2020 ).…”
Section: Dkd Therapy Targeting Oxidative Stress and Mitochondrial Fun...mentioning
confidence: 99%
“…Likewise, no hypoglycemia has been reported regarding linagliptin administration in normoglycemic animals, as seen in preclinical models of chronic kidney damage [ 27 ], inflammatory bowel disease [ 29 ], and an Aβ42-induced Alzheimer model [ 28 ]. Beyond its glucose modulating actions, linagliptin has demonstrated remarkable anti-inflammatory actions [ 27 , 29 ] and anti-apoptotic effects [ 30 , 31 ] in several pathological models in rodents. However, the potential ameliorative ability of linagliptin against cadmium-induced testicular injury has not been previously considered.…”
Section: Introductionmentioning
confidence: 99%